Use of Ablation Index-Guided Ablation Results in High Rates of Durable Pulmonary Vein Isolation and Freedom From Arrhythmia in Persistent Atrial Fibrillation Patients: The PRAISE Study Results. (September 2018) - Hussein, Ahmed; Das, Moloy; Riva, Stefania; Morgan, Maureen; Ronayne, Christina; Sahni, Ankita; Shaw, Matthew; Todd, Derick; Hall, Mark; Modi, Simon; Natale, Andrea; Dello Russo, Antonio; et al.
Abstract : Background: Catheter ablation for persistent atrial fibrillation (AF) is associated with less favorable outcomes than for paroxysmal AF. Substrate modification is often added to pulmonary vein isolation (PVI) to try to improve success rates. Recent studies have shown improved clinical outcomes with use of regional ablation index (AI) targets for PVI. We hypothesized that prospective use of AI-guided PVI in persistent AF patients would result in a low rate of PV reconnection at repeat electrophysiology study and that a high success rate can be achieved with durable PVI alone. Methods: Forty consecutive patients with persistent AF underwent AI-guided PVI with target values of 550 for anterior and 400 for posterior left atrial regions, followed by a protocol-mandated repeat procedure after 2 months. Patients were monitored for atrial tachyarrhythmia recurrence via daily plus symptom-initiated ECG recordings for 12 months. Recurrence was defined as ≥30 seconds of any atrial tachyarrhythmia after a 3-month blanking period. Results: PV reconnection was seen at repeat electrophysiology study in 22% of patients, affecting 7% of PVs. Ablation on the intervenous carina was required in 44% patients to achieve durable PVI. Atrial tachyarrhythmia recurrence was documented in 8 (20%) patients, only one of whom had PV reconnection at repeat study. At 12 months, 38/40 (95%) patients were in sinus rhythm, with 4 (10%) patients having started antiarrhythmic drugs. Higher body mass index and excess alcohol consumption were the only significant factors associated with atrial tachyarrhythmia recurrence. Conclusions: Use of AI targets results in a high level of durable PVI. A good clinical outcome can be achieved in the great majority of persistent AF patients with AI-guided PVI alone. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02628730.